2022
DOI: 10.1021/acs.jpcc.2c05268
|View full text |Cite
|
Sign up to set email alerts
|

Red-Light-Mediated Photocatalytic Hydrogen Evolution by Hole Transfer from Non-Fullerene Acceptor Y6

Abstract: We report the use of blend nanoparticles (NPs) of the organic semiconductors PM6 and Y6 for the photocatalytic production of hydrogen under sacrificial conditions, with a 2% mass loading of Pt cocatalyst. When prepared using TEBS, a thiophene-containing surfactant, these blend NPs have a desirable intermixed morphology. Under ≈1-sun illumination from 400 to 900 nm, hydrogen is produced at a rate of 8000 ± 400 μmol h–1 g–1. Remarkably, this rate remains high at 5200 ± 300 μmol h–1 g–1 under 650 to 900 nm excita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 51 publications
5
35
0
Order By: Relevance
“…This rate is ∼1.5 times lower than the rate reported by Kosco et al for TEBS-stabilized Y6 NPs . A lower rate is expected here as a lower Pt loading was used in this work (2% compared to 10%) for better comparison to other systems with Pt cocatalysts. ,, NPs stabilized with TEBS achieved an EQE of 0.054 ± 0.001% under 780 nm illumination (Figure b,c). In contrast to TEBS-stabilized Y6 NPs, Y6 NPs stabilized with SDS had a significantly lower H 2 evolution rate of 110 ± 20 μmol h –1 g –1 .…”
Section: Resultsmentioning
confidence: 41%
See 3 more Smart Citations
“…This rate is ∼1.5 times lower than the rate reported by Kosco et al for TEBS-stabilized Y6 NPs . A lower rate is expected here as a lower Pt loading was used in this work (2% compared to 10%) for better comparison to other systems with Pt cocatalysts. ,, NPs stabilized with TEBS achieved an EQE of 0.054 ± 0.001% under 780 nm illumination (Figure b,c). In contrast to TEBS-stabilized Y6 NPs, Y6 NPs stabilized with SDS had a significantly lower H 2 evolution rate of 110 ± 20 μmol h –1 g –1 .…”
Section: Resultsmentioning
confidence: 41%
“…The rate of H 2 evolution and EQE exhibited by the TEBS-stabilized Y6 NPs is significantly lower than that of organic donor:NFA systems. , Optimized TEBS-stabilized PM6:Y6 NPs have been shown to achieve an EQE of 5% at 800 nm . A more direct comparison under similar experimental conditions (identical light source, reactor, Pt loading and mass of Y6) found that TEBS-stabilized 1:1 PM6:Y6 NPs have an EQE of 0.22% at 780 nm, corresponding to an approximately 4-fold increase in EQE compared to neat TEBS-stabilized Y6 NPs . This decrease in performance for a single-component system is expected due to the loss of the bulk heterojunction structure, which provides a driving force for the separation of electrons and holes.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this alternate application, the nanoparticles can be used in water-based colloidal form, meaning the additional fabrication step of coating the nanoparticles to form a thin solid film is not necessary. 14 Non-fullerene acceptors (NFAs) have overtaken fullerene acceptors in organic photovoltaics and photocatalysis, [15][16][17][18][19] both BHJ and nanoparticulate, and the ability to map the morphology accurately is required for optimising structure-function relationships in device applications. In this report, we selected to study the new high performance donor-acceptor material systems PTzBI-Si:N2200 and PTQ10:IDIC, and the more well-known long-standing system TQ1:PC 71 BM, a fullerene containing system.…”
Section: Introductionmentioning
confidence: 99%